Stress as a Mediator of Authentic Happiness and Heroic Leadership on the Work Achievement of Nurses at Occupational Health Nursing - Antonius Dieben Robinson Manurung; Ambar Wahyuningsih Roestam; Yosephin Sri Sutanti (Dinasti Publisher, 2023)
This study aims to identify and analyze stress as a mediator of authentic happiness and heroic leadership on work performance of nurses at the Occupational Health Nurses Association during the Covid-19 pandemic. This study uses a quantitative approach with Structural Equation Modeling (SEM) Techniques - SmartPLS. The subjects in the study were occupational health nurses who were members of the Occupational Health Assistence Associations (ONI-OHN) with a total of 101 members. The sampling technique used in this study is a purposive sampling technique with non-probability sampling. The results of this study show the important influence of authentic happiness and heroic leadership as an effort to increase work performance with stress as a mediator, and the application of organizational and work psychology implications related to authentic happiness and heroic leadership as an effort to increase work performance with stress as a mediator